Intrapartum-related Perinatal Deaths in Births Planned in Midwifery-led Settings in Great Britain: Findings and Recommendations From the ESMiE Confidential Enquiry. Issue 3 (September 2021) - Rowe, R.; Draper, E.S.; Kenyon, S.; Bevan, C.; Dickens, J.; Forrester, M.; Scanlan, R.; Tuffnell, D.; Kurinczuka, J.J.
Abstract : ( BJOG . 2020;127:1665–1675) The UK has higher rates of stillbirth and neonatal mortality than similar countries. A 2015 UK-wide confidential inquiry, Mothers and Babies: Reducing Risk through Audits and Confidential Enquiries across the UK (MBRRACE-UK), identified key issues contributing to perinatal death, including inadequate maternal monitoring, errors in fetal monitoring, and failure to recognize the transition from the latent phase of labor to the active phase. The majority of deaths included in MBRRACE-UK occurred in hospital obstetric units (OUs), but the proportion of births occurring in midwifery-led settings in England is increasing. While there is no evidence that midwifery-led settings experience higher rates of intrapartum-related perinatal deaths compared with OU, contributing factors to perinatal deaths in midwifery settings may differ. Enhancing the safety of Midwifery-led births Enquiry (ESMiE) reviewed the quality of care in pregnancy, labor, birth, and postpartum in births resulting in intrapartum-related deaths in midwifery-led settings and compared the findings with those of MBRRACE-UK.